(untitled) (Scientific journal of the Fergana State University, 2023)
This article is based on the need to research new socio-cultural methods of society transformation. In it, it is revealed that the knowledge of women, possessing high morals in all respects, is important in the upbringing of children in the family, that is, in the upbringing of the young generation. A socio-philosophical analysis of the role of women in the transformation of society and socio-cultural technologies, and the fact that intelligent and advanced women in society make a great contribution to solving moral and educational problems not only in the family, but also in society.